"Case Study of the Sea Fence in Tangerang from a Legal Perspective: Environmental Impact and Maritime Jurisdiction Dispute in 2025." - Guruh Sugeng Mulyono; Hamzah Syadewan; Ria Tri Vinata (Jurnal Hukum dan Demokrasi (JHD), 2025)
This study examines the case of sea fence construction along the Tangerang coast in 2025, which has sparked legal, environmental, and maritime jurisdiction controversies. The sea fence was built without official permits and lacked environmental documents such as the Environmental Impact Assessment (AMDAL) and Marine Spatial Utilization Permit (KKPRL), highlighting weak oversight in the use of marine space. This study aims to analyze the legality of the sea fence construction, its impact on coastal environments and marine ecosystems, and the jurisdictional implications involving the central government, local authorities, and coastal communities. The findings indicate that the construction violated existing laws and regulations, potentially causing ecological damage and social conflict. This research underscores the importance of enforcing maritime